Reversion Instability in the Galactose operon of Escherichia coli - Morse, M. L. (1969)
The gal-3 mutation, which had been shown previously to produce unstable revertants, was combined in three instances with recA, a mutation which suppresses recombination. Unstable revertants were produced in the gal-3 recA recombinants qualitatively as frequently as in the absence of the recA gene, and it is concluded that a recombination mechanism is not the basis of the instability observed.